PENGARUH PEMBERIAN PUPUK GUANO DAN PUPUK SP-36 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) - Afrida, Elli; Lisdayani, Lisdayani; Aprilliya, Indah (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Bean plants are one of the groups of legumes that are popular with the public. In addition, beans are one of the sources of vegetable protein, vitamins A, B, and C found in their seeds. The demand for beans is increasing every year. Fertilization is an effort to increase the harvest of a plant cultivation. The use of organic fertilizers, both liquid and solid, can be a solution to reduce excessive application of inorganic fertilizers, because organic fertilizers can improve the physical, chemical, and biological properties of the soil. The purpose of this study was to determine the effect of giving Guano fertilizer and SP-36 fertilizer doses on the growth and yield of bean plants. This study used a Factorial Randomized Block Design with 2 factors: Factor l, namely Guano fertilizer (G) with 4 levels, namely: G0 = 0 g/plant (Control), G1 = 30 g/plant, G2 = 60 g/plant and G3 = 90 g/plant. Factor 2, namely the provision of SP36 (K) fertilizer with 4 levels, namely: K0 = Control (0 g/plant), K1 = 1.5 g/plant, K2 = 3 g/plant, K3 = 4.5 g/plant. The parameters observed in this study include plant height, number of branches, number of pods/plant and weight of pods/plant. The results of the study showed that the provision of Guano fertilizer had no significant effect on plant height, number of primary branches, number of pods and weight of pods. Guano fertilizer is a biological fertilizer that is given to add organic material to bean plants